Steer feeding for small farmers - Poole, William (My University, 1898)
Introduction: The beef industry is one of vast importance to the Kansas farmer, and especially to the small farmers. Kansas has peculiar advantages for beef production. Her wide, grassy plains furnish enormous quantities of feed during six months of the year, and the cultivated fields and tame grass meadows furnish feed for the remainder of the year. At the present time, there seems to be no other occupation that will give better results for the amount of labor than that of beef producing. The climate of Kansas is just cold enough to cause cattle to feed will in the winter time, and we are within easy reach of good markets for our flattened cattle. Most of the lands owners of this section of the country have their surplus capital increased in cattle, and depend on them for their livelihood; and the only question with these farmers is, how they are to produce a greater quantity or a better quality of beef with an increase of labor and feed. Here is one of the most important things relating to the industry. A man in this business has a great work before him. There is a vast field for improvement. It is an occupation that requires a great deal of skill, and it cannot be brought to perfection without deep study and close observation on the part of the manager.
Citation: Poole, William. Steer feeding for small farmers. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Beef Industry; Kansas Farmer; Climate; Surplus Capital; Theses; Manuscripts (documents)